Microbiological Landscape of Intensive Care Unit: A Retrospective Analysis of Bacterial Pathogens and Their Implications - Sukmantara, I Putu Bayu; Dewa Ayu Putu Diah Dharmayanti; Dewa Ngakan Gde Dwija Sanjaya (HM Publisher, 2024)
Introduction: The intensive care unit (ICU) is a high-risk environment for hospital-acquired infections (HAIs) due to the complex interplay of patient vulnerability, invasive procedures, and the selective pressure of antimicrobial use. Understanding the local epidemiology of bacterial pathogens is crucial for effective infection prevention and control strategies. This study aimed to characterize the bacterial profile in an ICU setting, providing insights into the prevalent pathogens and their potential implications for patient care. Methods: A retrospective cross-sectional study was conducted, encompassing patients admitted to the ICU of Bangli Hospital Bali in 2023 and 2024. Data on patient demographics, sample sources, and microbiological findings were collected from medical records. Samples included blood cultures, sputum cultures (from both endotracheal tubes and spontaneous expectoration), wound swabs, and other sterile site cultures. Microbiological identification was performed using standard laboratory techniques. Results: A total of 219 patients were included in the study. The most common sample source was blood culture (42.9%), followed by sputum culture from endotracheal tubes (39.3%). A significant proportion of cultures showed no growth (34.7%), highlighting the challenges in identifying causative pathogens in the ICU. Among the identified pathogens, Staphylococcus spp. was predominant (15.5%), followed by Stenotrophomonas maltophilia (9.6%) and coagulase-negative staphylococci (8.7%). The distribution of pathogens varied across sample sources, with Staphylococcus spp. being prevalent in sputum cultures from endotracheal tubes and Klebsiella pneumoniae in sputum cultures. Conclusion: This study underscores the dynamic nature of the microbiological landscape in the ICU. The predominance of Staphylococcus spp., Stenotrophomonas maltophilia, and other opportunistic pathogens emphasizes the need for robust infection prevention and control measures. Further research is warranted to explore the impact of these pathogens on patient outcomes and to optimize antimicrobial stewardship in this critical care setting.